Lifestyle Interventions Targeting Body Weight Changes during the Menopause Transition: A Systematic Review - Janet Jull; Dawn Stacey; Sarah Beach; Alex Dumas; Irene Strychar; Lee-Anne Ufholz; Stephanie Prince; Joseph Abdulnour; Denis Prud’homme (Journal of Obesity)
Objective. To determine the effectiveness of exercise and/or nutrition interventions and to address body weight changes during the menopause transition. Methods. A systematic review of the literature was conducted using electronic databases, grey literature, and hand searching. Two independent researchers screened for studies using experimental designs to evaluate the impact of exercise and/or nutrition interventions on body weight and/or central weight gain performed during the menopausal transition. Studies were quality appraised using Cochrane risk of bias. Included studies were analyzed descriptively. Results. Of 3,564 unique citations screened, 3 studies were eligible (2 randomized controlled trials, and 1 pre/post study). Study quality ranged from low to high risk of bias. One randomized controlled trial with lower risk of bias concluded that participation in an exercise program combined with dietary interventions might mitigate body adiposity increases, which is normally observed during the menopause transition. The other two studies with higher risk of bias suggested that exercise might attenuate weight loss or weight gain and change abdominal adiposity patterns. Conclusions. High quality studies evaluating the effectiveness of interventions targeting body weight changes in women during their menopause transition are needed. Evidence from one higher quality study indicates an effective multifaceted intervention for women to minimize changes in body adiposity.